Effects of biodiversity strengthen over time as ecosystem functioning declines at low and increases at high biodiversity. Issue 12 (19th December 2016) - Meyer, Sebastian T.; Ebeling, Anne; Eisenhauer, Nico; Hertzog, Lionel; Hillebrand, Helmut; Milcu, Alexandru; Pompe, Sven; Abbas, Maike; Bessler, Holger; Buchmann, Nina; De Luca, Enrica; Engels, Christof; et al.
Abstract: Human‐caused declines in biodiversity have stimulated intensive research on the consequences of biodiversity loss for ecosystem services and policy initiatives to preserve the functioning of ecosystems. Short‐term biodiversity experiments have documented positive effects of plant species richness on many ecosystem functions, and longer‐term studies indicate, for some ecosystem functions, that biodiversity effects can become stronger over time. Theoretically, a biodiversity effect can strengthen over time by an increasing performance of high‐diversity communities, by a decreasing performance of low‐diversity communities, or a combination of both processes. Which of these two mechanisms prevail, and whether the increase in the biodiversity effect over time is a general property of many functions remains currently unclear. These questions are an important knowledge gap as a continuing decline in the performance of low‐diversity communities would indicate an ecosystem‐service debt resulting from delayed effects of species loss on ecosystem functioning. Conversely, an increased performance of high‐diversity communities over time would indicate that the benefits of biodiversity are generally underestimated in short‐term studies. Analyzing 50 ecosystem variables over 11 years in the world's largest grassland biodiversity experiment, we show that overall plant diversity effects strengthened over time. Strengthening biodiversity effects were independent of the considered compartment (above‐ or belowground), organizational level (ecosystem variables associated with the abiotic habitat, primary producers, or higher trophic levels such as herbivores and pollinators), and variable type (measurements of pools or rates). We found evidence that biodiversity effects strengthened because of both a progressive decrease in functioning in species‐poor and a progressive increase in functioning in species‐rich communities. Our findings provide evidence that negative feedback effects at low biodiversity are as important for biodiversity effects as complementarity among species at high biodiversity. Finally, our results indicate that a current loss of species will result in a future impairment of ecosystem functioning, potentially decades beyond the moment of species extinction.